PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA UNTUK BARANG NON-ESENSIAL - Aliya Dinar Salsabila; Najma Auralia Ayu Nur Azizah (Integrative Perspectives of Social and Science Journal, 2024)
In the digital era, social interaction is not limited to direct communication, but has expanded to various online platforms. One of the growing phenomena is Electronic Word of Mouth (e-WOM), which takes the form of online user reviews on social media. e-WOM has a significant effect on consumption patterns, especially among the younger generation such as students who tend to be dependent on technology. Students are often exposed to information from people around them and also from influencers which will encourage students to make impulsive purchases, such as branded goods and personal accessories that are not really needed, and can also make students FOMO about the current trend.  This study aims to analyze the extent of the influence of e-WOM on purchase decisions of non-essential goods in college students. Through a quantitative approach and distributing questionnaires, it was found that e-WOM has a significant and valid influence on students purchasing decisions. This shows that social media comments have an important role in shaping students' consumption patterns.